TMIC-09. EXCITATORY SYNAPSES BETWEEN PRESYNAPTIC NEURONS AND POSTSYNAPTIC GLIOMA CELLS PROMOTE GLIOMA PROGRESSION. (5th November 2018) - Venkatesh, Humsa; Morishita, Wade; Geraghty, Anna; Tam, Lydia; Silverbush, Dana; Regev, Aviv; Vogel, Hannes; Suva, Mario; Malenka, Rob; Monje, Michelle
Abstract: Neuronal activity robustly regulates high-grade glioma growth. Here, we report that neuron-glioma interactions include bona fide synaptic communication. Glioma cell expression of synapse-related genes was confirmed at the single cell level in primary adult and pediatric glioma samples. Structural synapses between presynaptic neurons and post-synaptic glioma cells were identified by confocal and electron microscopy. Voltage clamp recordings from patient-derived glioma cells xenografted to the CA1 region of the hippocampus demonstrates AMPAR-mediated excitatory neurotransmission between presynaptic neurons and post-synaptic glioma cells with local electrode stimulation of inputs to the CA1 region. Millisecond timescale excitatory post-synaptic currents (EPSCs) were observed in approximately 10–20% of glioma cells xenografted to the hippocampus. In some patient-derived glioma xenograft models, a larger subpopulation of glioma cells exhibit a second electrophysiological profile with longer, ~1 sec depolarization in response to neuronal activity. These longer timescale depolarizations induced by neuronal input activity are blocked by gap junction inhibitors, supporting the concept that neuron to glioma excitatory neurotransmission can be communicated through gap junction-coupling in a network of glioma cells, such as observed with tumor microtube interconnections. As depolarization of normal neural precursor cells during development profoundly affects neural stem cell proliferation, we tested the hypothesis that neuron to glioma synapse-mediated depolarization promotes glioma growth. Using in vivo optogenetic techniques to depolarize patient-derived glioma xenografts expressing channelrhodopsin-2 (ChR2), we found that glioma cell depolarization robustly promotes proliferation. Further supporting the functional role of glutamatergic signaling through the AMPA receptor, expression of a dominant-negative AMPA receptor subunit robustly inhibits glioma xenograft growth. These findings define an unexpected integration of glioma cells into neural circuitry, identify excitatory synaptic neurotransmission as a mechanism driving glioma growth and elucidate the previously unexplored potential to target glioma circuit dynamics for therapy of these lethal cancers.